The Principal's Strategy for Improving the Professionalism of Public Madrasah Aliyah School Teachers - Annisa Silviani; Ainur Rahman; Hasyim Asy’ari (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to determine the principal's strategy for improving teacher professionalism at Aliyah Negeri 10 High School South Tangerang. This research uses qualitative methods. Data is collected through observation techniques, interviews, and document studies. Furthermore, it is analyzed with three activity flows: data reduction, data presentation, and conclusion drawing. The results of this study show that: (1) the principal's policy process in improving teacher professionalism has been running well. Laws and government regulations guide them. (2) The principal's strategy in improving teacher professionalism by carrying out training to improve teacher professionalism, academic supervision, evaluation of teacher performance, continuing postgraduate education, including teachers in seminars and workshops outside of school. (3) the principal's strategy for improving the professionalism of teachers has been working well. They are judged by the principal's academic supervision activities and teacher performance assessment results. (4) the obstacles of the principal in improving teacher professionalism, namely the time of teaching and learning activities clashing with activities to increase teacher professionalism. (5) supporting factors in improving teacher professionalism, namely the enthusiasm of teachers who want to participate in activities to increase teacher professionalism. s academic supervision activities and teacher performance assessment. (4) the obstacles of the principal in improving teacher professionalism, namely the time of teaching and learning activities clashing with activities to increase teacher professionalism. (5) supporting factors in improving teacher professionalism, namely the enthusiasm of teachers who want to participate in activities to increase teacher professionalism. s academic supervision activities and teacher performance assessment. (4) the obstacles of the principal in improving teacher professionalism, namely the time of teaching and learning activities clashing with activities to increase teacher professionalism. (5) supporting factors in improving teacher professionalism, namely the enthusiasm of teachers who want to participate in activities to increase teacher professionalism.